(untitled) (Intent Research Scientific Journal, 2023)
The digitization of the economy is causing serious problems for existing business models, including structural divisions of the banking system, which is currently undergoing transformation around the world. Customer focus and personalization of the offer are key components of a digital banking strategy. For its effective implementation, it is necessary to solve tasks aimed at the accumulated experience of customers, as well as the introduction of innovations that support the interests of customers. The article discusses the areas of application of digital technologies in the banking sector of Uzbekistan, as well as in the world’s leading banking structures, and highlights the problems and prospects of digitalization of banking business.